On sign-symmetric signed graphs - Ghorbani, Ebrahim (Ars mathematica contemporanea, 2020)
A signed graph is said to be sign-symmetric if it is switching isomorphic to its negation. Bipartite signed graphs are trivially sign-symmetric. We give new constructions of nonbipartite sign-symmetric signed graphs. Sign-symmetric signed graphs have a symmetric spectrum but not the other way around. We present constructions of signed graphs with symmetric spectra which are not sign-symmetric. This, in particular answers a problem posed by Belardo, CioabCioaba, Koolen, and Wang in 2018.
Keywords: predznačeni graf; signed graph; spectrum; spekter